2006
DOI: 10.1071/mf05077
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth, maturity, longevity and natural mortality of the shortfin mako shark (Isurus oxyrinchus) in New Zealand waters

Abstract: EXECUTIVE SUMMARY BishopShortfin mako sharks were aged by counting growth bands in sectioned vertebrae collected from recreational fishing competitions and the tuna longline fishery. Replicate counts were made from images taken under reflected light. No systematic ageing bias was present within or between readers and count precision was high. Growth is rapid in early years and quickly declines. Vertebral data showed that males and females grow at similar rates until age 7-9 years, after which the relative grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 27 publications
(42 reference statements)
3
74
2
Order By: Relevance
“…(F>F opt =0.12 for males and F>F opt =0.09 for females). Estimates for females are considered more relevant for population modelling, because aspects of female population dynamics, including age-specific and total life-time fecundity and mortality, determine the potential increase in population numbers (Bishop et al 2006). In the Gulf of Tunis, during the study period, the stock of S. umbra was slightly overexploited (E>0.4 and F>F opt ).…”
Section: Age and Growthmentioning
confidence: 99%
“…(F>F opt =0.12 for males and F>F opt =0.09 for females). Estimates for females are considered more relevant for population modelling, because aspects of female population dynamics, including age-specific and total life-time fecundity and mortality, determine the potential increase in population numbers (Bishop et al 2006). In the Gulf of Tunis, during the study period, the stock of S. umbra was slightly overexploited (E>0.4 and F>F opt ).…”
Section: Age and Growthmentioning
confidence: 99%
“…Zealand (Bishop et al, 2006). Size-at-maturity (L 50 ) in both species appears consistent with previous results despite the relatively absence of mature females in the current study.…”
Section: Discussionsupporting
confidence: 81%
“…Zealand (Bishop et al, 2006), Mediterranean Sea (Boero & Carli, 1979), northeast Pacific (Pawson & Vince, 1999), northwest Atlantic coast of USA (Baum et al, 2003) and Canada (Campana et al, 2005). A major difference between our study area and these other regions is in the measures taken to regulate the catch and landing of sharks.…”
Section: Discussionmentioning
confidence: 99%
“…One of the biological variables that has the most influence on population analysis of any species is age, since this is the basis for calculating mortality and productivity rates (Campana 2001). Most studies have reported deposition of one age ring per year for Shortfin Makos (Cailliet and Bedford 1983;Ribot-Carballal et al 2005;Bishop et al 2006;Natanson et al 2006;Semba et al 2009). We chose the growth parameters reported by Ribot-Carballal et al (2005) to estimate the age structure of the Shortfin Mako individuals, because those authors conducted their work in the same study area.…”
Section: Discussionmentioning
confidence: 99%